NFL, the tobacco homolog of FLORICAULA and LEAFY, is transcriptionally expressed in both vegetative and floral meristems. - Kelly, A J (1995)
The homologous genes FLORICAULA (FLO) of Antirrhinum and LEAFY (LFY) of Arabidopsis regulate the formation of determinate floral meristems. Transcripts of these single-copy genes are confined to floral meristems and some floral organs as well as to the leaflike bracts that subtend Antirrhinum flowers. Based on these observations, we hypothesized that the transcription of genes homologous to FLO and LFY in tobacco, a determinate plant in which the primary shoot apex is consumed in the production of a terminal flower, would serve as a molecular marker for floral commitment. Surprisingly, transcripts of the tobacco homologs NFL1 and NFL2 (Nicotiana FLO/LFY) were found not only in floral meristems, but also in indeterminate vegetative meristems. This implies that the transcriptional expression of the FLO/LFY homologous genes in the apical meristem is not sufficient for the initiation of floral meristem development. In addition, the transcript patterns of the NFL genes identified a previously undescribed subset of cells within the shoot apical meristem that may indicate unique functional compartmentalization. This suggests that, unlike FLO and LFY, which specify determinacy only during floral development, the NFL genes act to specify determinacy in the progenitor cells for both flowers and leaves.